Development and Evaluation of Piper sarmentosum -Based Kombucha: Fermentation, Bioactivity, and Sensory Acceptance - Le Bao Xuyen Nguyen; Anh Duy Do; Thach Phan Van (Polish Journal of Food and Nutrition Sciences)
Piper sarmentosum , renowned for its bioactive properties, was explored as a material for kombucha production. This study investigated P. sarmentosum -based kombucha (PSK), focusing on its phytochemical content, antioxidant and antibacterial activities, anti-amylase effects, and sensory attributes during a 21-day fermentation period. An increase was found in the total flavonoid content (TFC) of PSK from 6.02 mg QE/L at the start to 34.07 mg QE/L after 21 days of fermentation. Similarly, the total phenolic content (TPC) increased from 108.2 mg GAE/L to 266.2 mg GAE/L during the same period. Antioxidant activity of PSK, assessed through DPPH and ABTS assays, reached 0.33 µmol TE/mL and 0.51 µmol TE/mL, respectively, by day 21. While PSK did not show significant antibacterial activity against Escherichia coli and Salmonella typhi , it exhibited increased inhibition against Vibrio cholerae (inhibition zone dimeter of 18.3 mm) and Staphylococcus aureus (inhibition zone dimeter of 23.2 mm) by day 14, with a decrease by day 21. Additionally, α-amylase inhibition increased from 10.7% on day 0 to 15.4% on day 21. Sensory evaluations indicated that a 14-day fermentation period optimally balanced sweetness, sourness, and astringency of kombucha. Our study results indicate that P. sarmentosum is a promising substrate for preparing kombucha.